Editorial (Spring) Board? Gender Composition in High-impact General Surgery Journals Over 20 Years. Issue 3 (March 2019) - Harris, Chelsea A.; Banerjee, Tanima; Cramer, Monica; Manz, Shannon; Ward, Sarah T.; Dimick, Justin; Telem, Dana A.
Abstract : Objective: To quantify gender composition of 10 high-impact general surgery journals, delineate how board composition has changed over time, and evaluate qualification metrics by gender. Background: Underrepresentation of women on editorial boards may contribute to the gender-based achievement gap in surgery. Methods: We performed a cross-sectional analysis of the editorial board gender composition among 10 high-impact general surgery journals in 1997, 2007, and 2017. Univariate and multivariate regression analyses were used to assess differences in editors' H-indices, academic rank, and number of advanced degrees. Differences in editor turnover and multiple board positions were evaluated for each time interval. Results: Over 20 years, the proportion of women on editorial boards increased from 5% to 19%. After controlling for time since board certification, no differences between men and women's number of advanced degrees, H-indices, or academic rank remained significant. Women and men were equally likely to hold multiple board positions (1997 P = 0.74; 2007 P = 0.42; 2017 P = 0.69), but men's editorial board tenure was longer across each time interval (1997–2007 P = 0.003; 2007–2017 P < 0.001; 1997–2017 P = 0.01). Conclusions: Women surgeons have a small but growing presence on surgical editorial boards, and gender-based qualification differences are likely attributable to practice length. Men's longer tenure on editorial boards may drive some of the observed disparity by limiting new appointment opportunities. Strategies such as imposing term limits or instituting merit-based performance reviews may help editorial boards capture the field's changing demographics.